Encapsulation of superparamagnetic iron oxide nanoparticles with polyaspartamide biopolymer for hyperthermia therapy. (5th January 2020) - Nguyen, Minh Phuong; Nguyen, Minh Hoang; Kim, Jaeyun; Kim, Dukjoon
Graphical abstract: Highlight: Polyaspartamide (PA)-encapsulated SPIONs as nano-heaters for hyperthermia therapy. Enhancing biocompatibility and cellular uptake due to biotin functional group. Effective cancer killing in both in vitro and in vivo hyperthermia experiments. These results will open further potential for cancer treatment in the future. Abstract: We report a delicate synthesis process of polyaspartamide-encapsulated superparamagnetic iron oxide nanoparticles (PA-encapsulated SPIONs) with their sufficiently obtained grain-size below 100 nm for hyperthermia application. Iron oxide nanoparticles with a high magnetization have been applied as nano-heaters while polyaspartamide (PA) is a biocompatible and biodegradable polymer with a polysuccinimide (PSI) backbone. Multi-functional polymer PA could be conjugated with other groups such as biotin to enhance the uptake capability by receptors of cancer cells. Consequently, encapsulating SPIONs nano-heaters with PA biopolymer is an attractive roadmap for hyperthermia therapy application. Our results revealed that PA-encapsulated SPIONs showed excellent biocompatible behavior based on cell viability test. With Prussian blue staining of cancer cells (4T1), cellular uptake of PA-encapsulated SPIONs was significantly increased in the presence of biotin conjugated on the outer shell. Furthermore, PA-encapsulated SPIONs exhibited effective cancer killing activities in both in vitro and in vivo hyperthermia experiments. Therefore, PA-encapsulated SPIONs might have potential for hyperthermia therapy.